Promotion of mental health: care for adolescents with depressive symptoms in a school clinic (Research, Society and Development, 2022)
Adolescents form a vulnerable group to develop some psychological disorders, including depression, and the importance of mental health care for this public is recognized. This study aimed to identify the perception of adolescents with depressive symptoms regarding the benefits of care at a teaching clinic that offers psychological services in the city of Manaus-AM. This research has a qualitative approach in which 10 adolescents aged between 15 and 18 years old attended in 2020 and 2021 participated. Data collected in semi-structured interviews were analyzed according to thematic content analysis. The benefits identified were: increased self-esteem; benefits in the family relationship; benefits during a COVID 19 pandemic; decrease/absence of self-injury and other symptoms. These benefits may not mean a total remission of depressive symptoms, but there was a positive change in the adolescents' quality of life.